The Role of Financial Administration in the Quality of Education at SMK IT Architect Bengkulu City - Novianto, Chandra; Junaidi, Hamdan (Al-Khair Journal: Management Education, 2025)
Abstract: Financial administration plays an important and strategic role in determining the quality of education, especially in vocational secondary schools. This study aims to map, describe, and analyze the role of financial administration in educational quality at the Integrated Islamic Vocational High School of Architecture in Bengkulu City. Using a qualitative approach with data collection techniques consisting of observation, interviews, and documentation. The research findings indicate that financial administration plays an important role in determining the quality of education. Financial constraints and suboptimal budget planning have a direct impact on educational quality, including educational input, process, output, and outcomes. The role of financial administration is crucial in determining educational quality. Effective, transparent, and accountable financial management is a key factor in supporting the smooth implementation of the learning process, enhancing the professionalism of educators, and ensuring the availability of adequate educational facilities. Thus, it can be concluded that financial administration plays an important role in improving the quality of education in schools. Therefore, it is recommended that in order to enhance educational quality, the role of financial administration in schools should be strengthened.Keywords: The Role of Financial Administration, Quality of Education, SMK IT Arsitek. Abstrak: Administrasi keuangan memegang peran penting dan strategis dalam menentukan mutu pendidikan, terutama di sekolah menengah kejuruan. Penelitian ini bertujuan untuk memetakan, mendeskripsikan, dan menganalisis peran administrasi keuangan dalam mutu pendidikan di Sekolah Menengah Kejuruan Islam Terpadu Arsitek Kota Bengkulu. Menggunakan pendekatan kualitatif dengan teknik pengumpulan data observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa administrasi keuangan berperan penting dalam menentukan mutu pendidikan. Keterbatasan keuangan dan kurang optimalnya perencanaan anggaran berdampak langsung pada mutu pendidikan seperti; input, proses, output, dan outcome pendidikan. Peran administrasi keuangan sangat menentukan mutu pendidikan. Pengelolaan keuangan yang efektif, transparan, dan akuntabel menjadi kunci utama dalam mendukung kelancaran proses pembelajaran, peningkatan profesionalisme pendidik, serta ketersediaan fasilitas pendidikan yang memadai. Dengan demikian dapat disimpulkan bahwa administrasi keuangan berperan penting dalam meningkatkan mutu pendidikan di sekolah. Oleh karena itu, dapat disarankan bawa untuk meningkatkan mutu pendidikan, maka tingkatkan peran administrasi keuangan di sekolah.Kata kunci: Peran Administrasi Keuangan, Mutu Pendidikan, SMK IT Arsitek.